Etika Guru Menurut Perspektif Pendidikan Agama Islam - Yazidul Busthomi Syamsul A’dlom (STIT Muhammadiyah Paciran Lamongan, 2021)
According to the term, the language of ethics comes from the word ethos which means customs (habits), while in terms of ethics is the study of human behavior to determine the values ​​of good and bad deeds, while the measure to determine the value is the human mind or resio. Ethics is a whole of norms and judgments that are used by the society concerned to find out how humans should live their lives in a rational way. Ethics functions as an appraiser, determinant, determinant of an action carried out by humans, thus ethics plays a more role as a drafter of behavior carried out by humans. Among teacher ethics according to the perspective of Islamic religious education, namely: 1. Accepting questions raised by students, 2. Not rushing in all matters, 3. Sitting with dignity with calmness and bowing your head, 4. Not being arrogant to all humans, 5. Prioritizing tawadu 'in meeting places and assemblies, 6. Not playing and joking, 7. Showing affection for students when teaching.